Patients' Willingness to Trade Off Between the Duration and Frequency of Rheumatoid Arthritis Treatments. Issue 7 (July 2014) - Poulos, Christine; Hauber, A. Brett; González, Juan Marcos; Turpcu, Adam
<x xml:space="preserve">Abstract</x> Objective Biologic treatments for rheumatoid arthritis (RA) vary widely in both the time required to administer treatment and treatment frequency. This study aimed to quantify the rate at which RA patients are willing to trade off between the time required to administer treatment (duration) and treatment frequency. Methods Respondents with a self‐reported physician diagnosis of moderate to severe RA completed an online discrete choice experiment survey (also known as conjoint analysis). Respondents were presented with a series of treatment‐choice questions. Each hypothetical treatment included 6 attributes: response rate, mode of administration, treatment duration, treatment frequency, and the risks of immediate mild and serious treatment reactions. Preference weights, also called marginal utilities or relative importances, were estimated using mixed‐logit methods and then used to calculate the marginal rates of substitution between attributes, including treatment duration and treatment frequency. Results Among the 901 respondents, 505 were in the RA Information, Service, and Education group (www.risesupport.com) and 396 were members of an online panel. The marginal utility of changes in treatment features was largest for a 1‐hour change in treatment duration, while a 1‐unit change in the annual frequency of treatment was the second least important change. The marginal utility of changes in annual treatment frequency depends on the treatment duration and vice versa. Conclusion Respondents would accept treatments with lower efficacy and greater risk to achieve lower duration and frequency. Previous studies have linked patient preferences to treatment adherence, suggesting that reductions in duration or frequency could improve adherence and health outcomes.